1982
DOI: 10.1111/j.1365-2125.1982.tb01993.x
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular and platelet effects of epoprostenol (prostacyclin, PGI2) are unaffected by beta‐adrenoceptor blockade in man.

Abstract: 1 Atenolol 0.2 mg/kg i.v., propranolol 0.2 mg/kg i.v. or placebo were given in a double‐blind crossover study to six healthy male subjects, and the effects of a subsequent infusion of epoprostenol (prostacyclin, PGI2) 0‐6 ng kg‐1 min‐1 monitored. 2 PGI2 caused a tachycardia, a fall in diastolic blood pressure, a rise in pulse pressure, reduction in pre‐ ejection period (PEP) and rise in left ventricular ejection time index (LVETI), headache and facial flushing at doses of PGI2 greater than 2 ng kg‐1 min‐1, (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
(28 reference statements)
4
6
0
Order By: Relevance
“…The effects of PGI2 on blood pressure, pulse and the symptoms experienced by the subjects in the current study were similar to those found in previous work [12][13][14] and are discussed in more detail elsewhere. It seems likely that the headache frequently reported during PGI2 infusion is the result of vasodilation occurring in the external carotid circulation (as demonstrated by the facial flush), although the current results do not exclude the possibility that the headache results from changes in the calibre of larger intracranial vessels that are not reflected by alterations in cerebral perfusion.…”
Section: Brown Picklessupporting
confidence: 88%
“…The effects of PGI2 on blood pressure, pulse and the symptoms experienced by the subjects in the current study were similar to those found in previous work [12][13][14] and are discussed in more detail elsewhere. It seems likely that the headache frequently reported during PGI2 infusion is the result of vasodilation occurring in the external carotid circulation (as demonstrated by the facial flush), although the current results do not exclude the possibility that the headache results from changes in the calibre of larger intracranial vessels that are not reflected by alterations in cerebral perfusion.…”
Section: Brown Picklessupporting
confidence: 88%
“…The effect of various prostaglandins on STI have also been studied. Prostacyclin infusion produced a dose-related decrease in diastolic blood pressure, PEP and QS2I (Warrington, Smith and O'Grady, 1980) and an increase in LVETI (Hassan et al, 1982).…”
Section: Use Of Systolic Time Intervals In Clinical Pharmacologymentioning
confidence: 99%
“…The hypotension results from peripheral vasodilation (Eklund, et al, 1981) and the cause of the tachycardia is not yet clear (Hassan et al, 1982b). Although the hypotension is usually asymptomatic, it was listed as a side effect by Dowd et al.…”
Section: Pain In Limbs and Jawmentioning
confidence: 99%